IN SILICO STUDY OF TRITERPENOID IDENTIFIED FROM Ceriops decandra LEAVES AS INHIBITORS OF α-AMYLASE - Puspitasari, Yunita Eka; Tambunan, Jeny Ernawati; Hardoko, Hardoko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
α-amylase has a pivotal role in catalyzing the cleavage of α-1,4-glycosidic bonds of polysaccharides to produce oligosaccharides. The inhibition of α-amylase delays the breakdown of carbohydrates, causing a reduction of blood glucose levels absorption in diabetes patients. The exploration of α-amylase inhibitors has attracted because society assumed that utilizing herbal medicine reduced the side effect of prescribed drugs. Mangrove from genus Ceriops have been used as antidiabetic, but the mechanism as α-amylase inhibitors has not been reported. Consumption of leaves extract of C.decandra reduced blood glucose level in diabetic rats, and triterpenoids have been identified from the leaves. With this in mind, this study aims to predict the molecular interactions between α-amylase (PDB ID: 4GQR) and the inhibitors, triterpenoid identified in C.decandra leaves, and to evaluate the potency of triterpenoid as α-amylase inhibitor. There are five triterpenoids identified in C.decandra leaves used as ligand tests, including lupenone, betulin, betulonic acid, betulinic acid, and lupeol. The descriptive method was applied in this investigation. This study was carried out from June to September 2022. Based on the molecular interactions, the binding affinity of triterpenoids was lower than the native ligand and control ligand. Lupenone, lupeol, betalonic acid, and betulinic acid inhibited α-amylase activity by non-competitive inhibition. It was predicted that betulin inhibited α-amylase activity through competitive inhibition.